HUBUNGAN PENGGUNAAN APLIKASI BELANJA ONLINE DENGAN POLA HIDUP KONSUMTIF MAHASISWA DI JURUSAN PENDIDIKAN MASYARAKAT UNIVERSITAS NEGERI MEDAN - Melani, Putri (JPUS: Jurnal Pendidikan Untuk Semua, 2023)
Abstract: The purpose of this study was to determine the relationship between the use of online learning applications and the consumptive lifestyle of students majoring in community education. This type of research is descriptive correlation. Correlation descriptive research is a way to determine the level of relationship between two or more variables without making additional changes and manipulation of existing data. The location of this research is in the Public Education Department of Medan State University. When this research was conducted from October 2022 to December 2022. The sample for this research was 35 students. Based on the product moment correlation analysis, there is a positive and significant relationship between consumptive lifestyle (Y) on the use of online shopping applications (X). Thus the price of rcount > rtable is 0.57 > 0.27. So it can be concluded that there is a significant relationship between the use of online shopping applications and the consumptive lifestyle of students in the Public Education Department, Medan State University. The results of the calculation of the coefficient of determination obtained Kd = r^2 x 100% = ?(0.323)?^2 x 100% = 10.43% The consumptive lifestyle of students in the public education department is influenced by the use of online learning applications, the remaining 89.57% is influenced by other variables. Keywords: Keywords: Applications, Online Shopping, Consumer Lifestyle.